2015
DOI: 10.1111/ane.12376
|View full text |Cite
|
Sign up to set email alerts
|

Patients with manifest hepatic encephalopathy can reveal impaired thermal perception

Abstract: The present findings demonstrate an impairment of temperature perception in HE. The extent of this impairment correlates with HE severity as quantified by the CFF. The attenuation of the correlations after correction for attention deficits suggests a strong role of attention deficits for the impaired thermal perception. Thus, it provides initial evidence for a central impairment of thermal processing in HE due to alterations in high-level processes rather than due to peripheral neuropathic processes, which are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
1
4
1
Order By: Relevance
“…Our results are in contrast with a previous study from Brenner et al [ 24 ] where the hand was used as the test site, the result of which found impaired thermal perception in grade 2 HE patients, but no differences in MHE patients. They concluded that these alterations emerge mainly in advanced stages of the disease.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results are in contrast with a previous study from Brenner et al [ 24 ] where the hand was used as the test site, the result of which found impaired thermal perception in grade 2 HE patients, but no differences in MHE patients. They concluded that these alterations emerge mainly in advanced stages of the disease.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies using neurophysiological methods have found impairments in both central and peripheral parts of the somatosensory system in patients with liver cirrhosis and overt HE [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our results demonstrate that this disease-related impairment does also span the somatosensory modality, and particularly the temporal discrimination of tactile stimuli. This finding tallies with early work showing both sensory impairments on the behavioral level in HE ( Brenner et al, 2015 ) and slowing of cortical oscillatory activity within the somatosensory system in this patient population ( May et al, 2014 ). Moreover, the correlation of CFF and criticalSOA implies that the severity of the impairment of tactile temporal perception parallels the impairments of visual temporal perception.…”
Section: Discussionsupporting
confidence: 89%
“…The present observations revealed enhanced PTN and RNA oxidation in brain regions of Glul fl/fl × Alb-Cre + mice, whose function is compromised in HE. Functions affected in HE include memory formation in the hippocampus (44); processing of sensory stimuli, such as perception, in the somatosensory cortex (45); and motor functions in the cerebellum (46). Interestingly, in the cerebellum of mice lacking hepatic GS, we identified exceptionally high levels of oxidized RNA in Purkinje cells, which critically control motor functions (30).…”
Section: Discussionmentioning
confidence: 95%